Business Models, Including Higher Value Products for the New Circular, Resource-Efficient Biobased Industry - Lange, Lene (Frontiers in Sustainability, 2022)
Types of Business Models for the new circular, resource-efficient biobased industry & SME By Lene Lange, Bioeconomy, Research & Advisory Abstract The biobased-business model, initiated the era of improved use of biological resources, upgrading resources otherwise wasted or downgraded, started with the “biomass to biofuel” biorefinery: Economy by scale, requiring large investments and stable supply of high volume, low-cost feedstock. A high profiled business model for pioneering biorefineries was the Joint Venture, often formed by two already mature businesses, joining different sets of competence, skills and experience; with opportunity for merger or acquisition. The biofuel biorefinery was challenged from two sides, its commercial viability (caused by low-priced end-product) and sustainability issues, utilizing only the energy content and not the biomass structures. A new era of biobased industries were started, focusing on unlocking full potential of the biomass, by cascading optimized valorization of all (or at least more parts of) the biomass components. This dual objective, opens for a spectrum of new types of bioeconomy business models, suitable for more complex biobased industries, including higher-value products in the biobased portfolio, being more complex, handling several more process-steps and -streams, and producing several types of biobased products. Five examples of such business models are described: 1. Biobased industry, upgrading in-house production side-streams. 2. The Stand-alone biorefinery. 3. Cooperatively owned biobased valorization of crop residues and processing sidestreams. 4. Industry clusters as the preferred biobased business model. 5. Local consortium-owned production of biobased products. Lastly, business models, suitable for biobased industries is presented.